"When They Come for You": Legal Mobilization in New Authoritarian Russia. Issue 2 (10th May 2018) - van der Vet, Freek
Abstract : As of 2012, the Russian State Duma passed a string of repressive laws on nongovernmental organizations (NGOs), surveillance, and high treason. Under this "new authoritarian" regime, a growing number of Russians are investigated by the security services or put on trial for high treason. NGOs face selective prosecution and surprise inspections. While we know how lawyers use legal mobilization in democratic regimes where they can expect courts to be fair, legal mobilization remains understudied in regimes moving toward authoritarianism, where authorities pass repressive laws but enforce them erratically. Drawing on interviews with Russian lawyers, this article examines how lawyers represent two victim groups of state coercion: Russians under investigation for treason and prosecuted human rights NGOs. By examining how lawyers make strategic choices while coping with unfair courts, the random enforcement of laws, and shrinking resources, this article argues that state coercion does not deter lawyers from legal mobilization at domestic courts and the European Court of Human Rights. Instead, repressive laws push lawyers to reinvent their everyday practices to counter repressive legislation and conviction bias in the criminal justice system.